Galactic nuclear off-centerings: the innermost accretion mechanism?. Issue Volume 15:Issue S359(2020) (March 2019) - Gaspar, Gaia; Díaz, Rubén; Mast, Damían; Agüero, María P.
Abstract: In the current scenario of galaxy evolution, supermassive black holes (SMBH) are present in almost all galaxies. To trigger nuclear activity, large amounts of material have to fall from kpc to pc and even smaller scales. Hence, an efficient angular momentum removal mechanism is needed. A growing black hole could still not be fixed in the gravitational potential well of the galaxy. This can be observed as a break in the symmetry between the global structure of the galaxy and the central source and could be part of the mechanism that drives material from the last hundred parsecs onto accretion in the SMBH. We present spatial profile decomposition of 16 galaxies observed with GNIRS (Gemini North) in the K long band. We have been able to measure off-centerings in 3 of 16 galaxies. We found a possible correlation between the presence of an off-centering and the SMBH mass.